2020
DOI: 10.3390/foods9030342
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Breed and Diet Type on the Freshness and Quality of the Eggs: A Comparison between Mos (Indigenous Galician Breed) and Isa Brown Hens

Abstract: Eggs are a nutritious food, offering a balanced source of essential amino and fatty acids, minerals, and vitamins. Genetic and diet factors can modify hen egg traits. Thus, the effects of breed and feed on egg quality using two laying hens, Mos (autochthonous breed) and Isa Brown (commercial hybrid), and three feeds, commercial fodder (CF), corn/pea/triticale (CPT) and corn/wheat (CW), were investigated. Freshness parameters (egg weight, eggshell weight and thickness, albumen height, Haugh units and yolk color… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 39 publications
5
30
0
Order By: Relevance
“…The morphometric measurements show highly significant sexual dimorphism, due to hormonal growth effects [ 39 ], in accordance with several authors [ 17 , 18 , 19 , 20 , 22 , 24 , 40 , 41 , 42 , 43 , 44 ]. Breed had significant effect ( p ≤ 0.05) in males, with the superiority of the “Branca” roosters, being the heaviest, largest and with the highest shank diameter and the “Preta Lusitânica” roosters, the lightest, shortest and with the smallest chest circumference.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The morphometric measurements show highly significant sexual dimorphism, due to hormonal growth effects [ 39 ], in accordance with several authors [ 17 , 18 , 19 , 20 , 22 , 24 , 40 , 41 , 42 , 43 , 44 ]. Breed had significant effect ( p ≤ 0.05) in males, with the superiority of the “Branca” roosters, being the heaviest, largest and with the highest shank diameter and the “Preta Lusitânica” roosters, the lightest, shortest and with the smallest chest circumference.…”
Section: Discussionsupporting
confidence: 85%
“…The sustainability of production is becoming an increasingly strong consumer argument for the choice of products and producers that are part of their diet [ 17 , 18 , 19 ]. The breeding system for indigenous species is balanced by the use of natural resources, land and water, making it environmentally “friendlier”, and particularly adjusted in less favored regions where these resources are scarce [ 16 , 20 , 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…The most common egg quality characteristics are egg shape index, breaking strength, shell thickness, specific gravity, albumen height and weight, pH of albumen and yolk, Haugh unit and oxidative status of yolk lipids [30,31]. Despite having a significant effect on Haugh unit, albumen height, eggshell thickness, and egg surface area (p < 0.05), other egg traits were not influenced (p > 0.05) by VE or Se supplementation ( Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, several studies had demonstrated that local breeds (e.g., Mos, Polverara, Black-Boned, Thai Native) are known for their great rusticity, allowing them a better adaptation to different diets and production systems than those showed by hybrids (Zotte et al, 2020;Franco et al, 2016Franco et al, , 2020Jaturasitha et al, 2008;Pateiro et al, 2018).…”
mentioning
confidence: 99%